2022
DOI: 10.14715/cmb/2021.67.5.39
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of combined detection of serum Tg, IFN - γ and TgAb in thyroid adenoma

Abstract: This study aimed to explore the value of combined detection of serum thyroglobulin (Tg), interferon - γ (IFN - γ) and thyroglobulin antibody (TgAb) in the diagnosis and prognosis of thyroid adenoma (TA). For this purpose, 100 patients with TA in our hospital from January 2017 to December 2020 were selected as the observation group, and they were divided into good prognosis group (83 cases) and poor prognosis group (17 cases) according to the surgical treatment; another 50 healthy people who received physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
3
1
Order By: Relevance
“…[23] Elevated Tg-Ab levels may indicate heightened immunoreactivity, possibly linked to an increased risk of recurrence or metastasis in DTC patients. [24] Notably, the present study found no significant difference in the levels of FT3 and FT4 between the good and poor prognosis groups, which may be related to several factors. First, thyroid hormones are precisely regulated by the hypothalamicpituitary-thyroid axis, and the negative feedback mechanism helps to maintain FT3 and FT4 at relatively stable levels.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…[23] Elevated Tg-Ab levels may indicate heightened immunoreactivity, possibly linked to an increased risk of recurrence or metastasis in DTC patients. [24] Notably, the present study found no significant difference in the levels of FT3 and FT4 between the good and poor prognosis groups, which may be related to several factors. First, thyroid hormones are precisely regulated by the hypothalamicpituitary-thyroid axis, and the negative feedback mechanism helps to maintain FT3 and FT4 at relatively stable levels.…”
Section: Discussioncontrasting
confidence: 66%
“…[23] Elevated Tg-Ab levels may indicate heightened immunoreactivity, possibly linked to an increased risk of recurrence or metastasis in DTC patients. [24]…”
Section: Discussionmentioning
confidence: 99%
“…Starting with the approval of GLP-1RAS, there have been many discussions about the potential safety of GLP-1RAs for the treatment of diabetes, since it may induce thyroid disease. Although GLP-1RAs can effectively control blood sugar and reduce body weight, based on research on rodents during the drug development stage, people have raised concerns about the occurrence of medullary thyroid carcinoma (MTC) (10)(11)(12)(13). Therefore, in the United States, labels of GLP-1RAs product contain a black box warning.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the activation of GLP-1R can increase the amount of cyclic adenosine monophosphate in C-cells, which leads to the secretion of intracellular calcitonin, which promotes the proliferation and carcinogenesis of C-cells (16,17). Although calcitonin is a critical biomarker for MTC existence (13,18,19), it was not found that GLP-1RAs mediates elevation of calcitonin in non-human primates (17,18) or patients with type 2 diabetes (20,21). In view of these findings, we need to comprehensively and scientifically balance the benefits and possible risks of GLP-1RAs treatment in diabetes.…”
Section: Discussionmentioning
confidence: 99%